Pengaruh Penggunaan Media Sosial dan Komunikasi Keluarga Terhadap Perilaku Cyberbullying pada Anak - Uldafira, Aini; Rochmaniah, Ainur (Universitas Prof. Dr. Moestopo (Beragama), 2023)
The use of social media is increasingly growing among the wider community, especially among children. The presence of social media can certainly have positive and negative impacts. This is what is worth paying attention to because the use of social media is widely used by children for various needs that have an impact on themselves. Not only that,family communication also greatly influences children’s behavior and attitudes in terms of good or bad, such as behavior that hurts other people or can be called cyber bullying behavior. The aim of this research is to determine the use of social media and family communication on cyber bullying behavior in children . the researcher used a quantitative method which will be carried out on 128 respondents who are elementary school children in Sidoarjo sub-district which has been carried out in two schools , namely SDN 1 celep Sidoarjo and SD cendekia Sidoarjo with each school taking classes 5 and 6 and analyzed by validity, reability and multiple linear regression tests using SPSS. The results showed that the use of social media by 8,92% and family communication by 60,40% had a significant effect on cyberbullying behavior in children.